Green Synthesis and Characterization of Carbon Nanotubes/Polyaniline Nanocomposites - Van Hoa Nguyen; Jae-Jin Shim (Journal of Spectroscopy)
Carbon nanotubes/polyaniline (CNT/PANI) nanocomposites were synthesized by the interfacial polymerization of aniline in the presence of CNTs using two green solvents, water and an ionic liquid (1-butyl-3-methylimidazolium tetrafluoroborate, [bmim][BF4]), as the two phases. The formation and incorporation of PANI on the surface of the CNTs were confirmed by scanning electron microscopy, transmission electron microscopy, X-ray diffraction, Fourier transform infrared spectroscopy ultraviolet-visible spectroscopy, and X-ray photoelectron spectroscopy. The analyses showed that the surface of the CNTs was coated with different morphologies of thin PANI layers depending on whether a HCl or HNO3 solution was used. The thermal stability of the composites was much better than that of the bare CNTs and pure PANI. The as-prepared composites were also used to modify the nickel foam electrodes for characterization of the electrochemical properties.